The diversity perspective in the spectrum approach - Sándor-Schmidt, Barbara (Autonomy and Responsibility Journal of Educational Sciences, 2022)
The Theory of Multiple Intelligences is proposed by Howard Gardner in his 1983 book Frames of Mind: The Theory of Multiple Intelligences. Gardner articulated eight criteria for a behavior to be considered an intelligence. In the present research I observe the relating Project Zero research team’s results published in Building on Children’s Strengths, Project Zero Frameworks for Early Childhood Education, The Experience of Project Spectrum and Project Zero. I intend to explore the implementation possibilities of the method in Hungarian preschool education. Furthermore I demonstrate the games and activities which are connected to the method. I investigate the games, activities, and analyze the introductions, the curriculum, the scoring criteria, the observation sheets, the summary sheets, and the profiles. Introducing my results I present the fi rst steps of the application procedure.